2020
DOI: 10.1021/acsomega.0c04467
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Reducing Sugars Based on the Qualitative Technique of Benedict

Abstract: Determination of reducing sugars is carried out routinely in the food industry, in biological research, or pharmaceutical and biomedical quality control to estimate metabolically assimilable sugars. Widespread detection methods are complex, expensive, or highly polluting. Here, we propose the use of spectrophotometric quantification for reducing sugars (Benedict q ) based on the qualitative method of Benedict. The protocol was validated, to verify its reproducibility and precision. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 12 publications
1
16
0
2
Order By: Relevance
“…(3), it was observed that the optimum wavelength was 740 nm for all the seven different samples tested. A similar result was reported by [16], who tested a wide range of wavelengths (490-890 nm) and also reported 740 nm as the optimum wavelength for Benedict's reagent. Fig.…”
Section: Resultssupporting
confidence: 86%
“…(3), it was observed that the optimum wavelength was 740 nm for all the seven different samples tested. A similar result was reported by [16], who tested a wide range of wavelengths (490-890 nm) and also reported 740 nm as the optimum wavelength for Benedict's reagent. Fig.…”
Section: Resultssupporting
confidence: 86%
“…Seven-day-old R. dentatus seedlings were used for the extraction and determination of carbohydrates as reducing sugar (Hernández-López et al, 2020), soluble protein (Singh et al, 2015), and total amino acids (Lee et al, 2013).…”
Section: Determination Of Primary Metabolitesmentioning
confidence: 99%
“…Benedict’s reagent used for spectrophotometric measurements contains copper­(II) sulfate, sodium citrate and sodium carbonate only . The free carbonyl group of the glucose molecule reduces the copper ion followed by precipitation of copper­(I) oxide …”
Section: Approachmentioning
confidence: 99%